Predicting Survival After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Appendix Adenocarcinoma. Issue 7 (July 2018) - Aziz, Omer; Jaradat, Ihab; Chakrabarty, Bipasha; Selvasekar, Chelliah R.; Fulford, Paul E.; Saunders, Mark P.; Renehan, Andrew G.; Wilson, Malcolm S.; O'Dwyer, Sarah T.
Abstract : BACKGROUND: Appendix adenocarcinomas are rare tumors with propensity for peritoneal metastasis. Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy is an established treatment with curative intent, but, to date, studies reporting survival have been heterogeneous with regard to their patient groups (including other tumor types), interventions (not all patients receiving intraperitoneal chemotherapy), and follow-up (varying surveillance protocols). OBJECTIVE: The aim of this study is to quantify the impact of this intervention on survival in a homogeneous group of patients with appendix adenocarcinoma receiving standardized treatment and follow-up, and to determine the impact of prognostic indicators on survival. DESIGN: This is a retrospective analysis of a prospective database at a national peritoneal tumor center where all patients had their appendix pathology reviewed and management planned by a specialized peritoneal tumor multidisciplinary team. MAIN OUTCOME MEASURES: Data were extracted on prognostic indicators including peritoneal cancer index, completeness of cytoreduction score, preoperative tumor markers, and histological features. Overall and disease event-free survival from the date of intervention were evaluated using Kaplan Meier curves and univariate Cox proportional hazards regression analysis. RESULTS: A total of 65 patients underwent cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for appendix adenocarcinoma between 2005 and 2015. Median follow-up was 44.3 months. The overall survival was 55.5% and disease event-free survival was 36.1% (5-year rate). Peritoneal Cancer Index <7, complete cytoreduction score of 0, and preoperative CEA of <6 were all associated with significantly higher overall and disease event-free survival. CA19-9 <38 and CA125 <31 were not associated with a significantly higher overall or disease event-free survival. LIMITATIONS: The sample size was limited because of the rarity of this tumor type. CONCLUSIONS: This study quantifies the impact of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy on overall and disease event-free survival for appendix adenocarcinoma, identifying key prognostic indicators that may guide treatment. It supports the referral of these rare tumors to specialist centers with appropriate expertise for initial management and follow-up. SeeVideo Abstract athttp://links.lww.com/DCR/A595 .